Conserved nucleocytoplasmic density homeostasis drives cellular organization across eukaryotes - Abin Biswas; Omar Muñoz; Kyoohyun Kim; Carsten Hoege; Benjamin M. Lorton; Rainer Nikolay; Matthew L. Kraushar; David Shechter; Jochen Guck; Vasily Zaburdaev; Simone Reber (Nature Communications)
Abstract The confinement of macromolecules has profound implications for cellular biochemistry. It generates environments with specific physical properties affecting diffusion, macromolecular crowding, and reaction rates. Yet, it remains unknown how intracellular density distributions emerge and affect cellular physiology. Here, we show that the nucleus is less dense than the cytoplasm and that living systems establish a conserved density ratio between these compartments due to a pressure balance across the nuclear envelope. Nuclear transport establishes a specific nuclear proteome that exerts a colloid osmotic pressure, which, assisted by chromatin pressure, increases nuclear volume. During C. elegans development, the nuclear-to-cytoplasmic density ratio is robustly maintained even when nuclear-to-cytoplasmic volume ratios change. We show that loss of density homeostasis correlates with altered cell functions like senescence and propose density distributions as key markers in pathophysiology. In summary, this study reveals a homeostatic coupling of macromolecular densities that drives cellular organization and function.